2019
DOI: 10.1098/rsos.190841
|View full text |Cite
|
Sign up to set email alerts
|

Reverting ontogeny: rapid phenotypic plasticity of colour vision in cichlid fish

Abstract: Phenotypic plasticity, particularly during development, allows organisms to rapidly adjust to different environmental conditions. Yet, it is often unclear whether the extent and direction of plastic changes are restricted by an individual's ontogeny. Many species of cichlid fishes go through ontogenetic changes in visual sensitivity, from short to long wavelengths, by switching expression of cone opsin genes crucial for colour vision. During this progression, individuals often exhibit phenotypic plasticity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Additional spectral sensitivities found by MSP in A. ocellaris included one rod with a λmax value of 502 nm and four double cone spectral sensitivities with λmax values of 497 nm, 515 nm, ~535 nm, and a possible fifth cone with a λmax value of ~508 nm. We assume that A. ocellaris SWS opsins are only expressed in single cones, while the longerwavelength sensitive RH2 and LWS genes are strictly-expressed in the double cones, as has been found in the anemonefish, A. akindynos (Stieb et al 2019) and in cichlid fishes (Carleton et al , 2008Parry et al 2005;Spady et al 2006;Dalton et al 2015;Härer et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Additional spectral sensitivities found by MSP in A. ocellaris included one rod with a λmax value of 502 nm and four double cone spectral sensitivities with λmax values of 497 nm, 515 nm, ~535 nm, and a possible fifth cone with a λmax value of ~508 nm. We assume that A. ocellaris SWS opsins are only expressed in single cones, while the longerwavelength sensitive RH2 and LWS genes are strictly-expressed in the double cones, as has been found in the anemonefish, A. akindynos (Stieb et al 2019) and in cichlid fishes (Carleton et al , 2008Parry et al 2005;Spady et al 2006;Dalton et al 2015;Härer et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…to which extent cell type number and/or opsin expression within these cell types contribute to visual perception. Finally, phenotypic plasticity is known to strongly affect opsin expression (e.g., Härer et al, 2019; Hofmann, O'Quin, Smith, et al, 2010; Nandamuri et al, 2017). While we aimed here to avoid any bias due to plasticity by first acclimatizing studied cichlid species to laboratory light conditions in order to compare the genetically determined portion of these diverse species' visual systems (Carleton et al, 2016; Nandamuri et al, 2017), studies comparing cichlid species' performances within a specific field setup can also sample environmental parameters and fish retinas simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Further simplifications include the negligence of chromophore usage (A1/A2 ratio, though its effect on the visual systems of Lake Malawi cichlids is probably small, Carleton & Kocher, 2001), the structuring of cones in single‐ and double cones and potential shifts in diurnal cycle between opsin classes, although recent studies reveal that standardizing using overall opsin expression is a valid approach, especially as samples were processed in the early afternoon (Yourick et al, 2019). Furthermore, we do not account for opsin expression variation during ontogeny (only sexually mature fish were used and, among those, no relationship of opsin expression and age could be found) or due to plasticity (e.g., Härer et al, 2019; Hofmann, O'Quin, O'Quin, Smith, & Carleton, 2010; Nandamuri et al, 2017), although a minimum of 2 weeks acclimatization to artificial lighting was used to avoid bias in plasticity. Additionally, measuring physiological variables (opsin expression, lens transmission) can only approximate visual capabilities while actual visual capabilities can only be determined using behavioural approaches (e.g., Escobar‐Camacho, Marshall, & Carleton, 2017; Escobar‐Camacho, Taylor, et al, 2019; Kalb, Schneider, Sprenger, & Michiels, 2015; Kelber, Vorobyev, & Osorio, 2003; Kröger, Knoblauch, & Wagner, 2003; Schluessel, Fricke, & Bleckmann, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent study showed that opsin coexpression might be a novel mechanism for modulating color vision [22]. However, it is unclear whether the direction and extent of opsin expression plasticity are limited by ontogeny [23].…”
Section: Plastic Opsin Expression Was Reported To Have a Profound Effmentioning
confidence: 99%